Robotic Eye System for Animatronic Faces in Human-Robot Interaction - Rocha, Marina Z.; Maurell, Igor P.; Kappel, Kristofer S.; Drews, Paulo L. J.; Guerra, Rodrigo S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
Anthropomorphism plays a crucial role in Human-Robot Interaction (HRI), as nonverbal cues, such as eye gaze and facial expressions, significantly influence social perception. Among facial features, the eyes are particularly important, as they convey emotion and indicate the focus of attention. This work presents the development of a compact and functional animatronic eye system designed to improve an existing mechanism integrated into the robotic face of a domestic service robot. The current system, which mechanically links both eyes, limits expressiveness and restricts natural movement. To address these issues, two alternative mechanisms were explored: ABENICS and a system inspired by the HITSZ-Snakebot II robot. These were developed through CAD modeling and fabricated using both FDM and DLP 3D printing techniques. Three prototypes were created-two based on ABENICS and one on the snakebot design. The final prototype, based on the snakebot model, proved to be the most effective, offering a greater angular range, size reduction, and smoother, more natural movements. Its modular, compact structure makes it suitable for integration into expressive robotic faces, contributing to the development of more relatable and socially capable robots.